A Code Development for PWR Efficiency Analysis and Energy Conversion Process Simulator - Utaja Utaja; Arjoni Amir; Elfrida Saragi (Indonesian Journal of Physics, 2010)
Nuclear Power Plant is the energy producer which converts the nucleus binding energy to heat energy and then converts to the electrical energy. The conversion process from heat energy to the mechanical energy and then becomes to the electrical energy, is an important process. The main problem is how much the heat energy can be converted to the work which is known as the efficiency of the energy conversion. The other problem is how the energy- conversion process on the turbine-steam generator system takes place. The efficiency analysis includes the saturated steam data reading, and repeating calculation, which are very tedious if they are done by manual calculation. In such a manner, the energy conversion process includes the efficiency conversion, nozzel process, and valve calculation, therefore a computer code for calculation process is needed. This research is directed to a computer code development for the heat to work conversion analysis and for heat conversion process simulation. This software is based on the Rankine cycle of saturated steam, the nozzel thermodynamics on open cycle, and the fluid flow in the valve. Among the input processes are the steam pressure on the turbine inlet, the vacuum pressure in the condenser, the amount of the regenerator, the electrical power, and the reheater temperature. The result is displayed as entropy versus temperature graphical, which shows the variation of pressure, temperature, and the steam flow rate along the Rankine cycle. The total steam flow rate for a certain power is also displayed on the monitor. This variable is also displayed in the block diagram of the simulator. The pressure, temperature, and the steam consumption determine the amount of the total thermal energy which should be generated in the reactor core, determine the turbine and pipe size, where these variables are used on the next design process step. Using this software, the energy conversion calculation on the nuclear power plant could be done easier and faster.